Numerical Study on the Disturbance Effect of Short-Distance Parallel Shield Tunnelling Undercrossing Existing Tunnels - Zhen Huang; Chenlong Zhang; Helin Fu; Huangshi Deng; Shaokun Ma; Jiajun Fu (Advances in Civil Engineering)
The construction of new tunnels poses a threat to the operational safety of closely existing tunnels, and the construction mode of parallel undercrossing over short distances has the most significant impact. In this study, a new double-line shield tunnel parallel undercrossing of existing tunnels in Hefei, China, is taken as an example. A three-dimensional (3D) numerical model using FLAC3D finite difference software was established. The dynamic construction of the new double-line shield tunnel undercrossing the existing subway tunnel over a short distance and in parallel was simulated. The pattern of existing tunnel settlement and change in lining stress caused by the shield tunnelling process were analyzed. The reliability of simulation was verified through field-monitoring data. Finally, based on the numerical model, the effects of change in stratum sensitivity on the settlement of existing tunnel, lining internal force, and surface settlement are discussed. The results show that during shield tunnelling, the maximum ground settlement is 3.9 mm, the maximum settlement at the arch waist of existing tunnel near the new tunnel is 7.75 mm, and the maximum vault settlement is 5.38 mm. The maximum stress of lining of existing tunnel before the excavation is 7.798 × 105 Pa. After the construction of double-line shield tunnel, the maximum stress of lining is 1.124 × 106 Pa, an increase of 44% than that before the construction. The surface settlement and tunnel settlement are sensitive to the weakening of soil layer strength, and lining stress is not affected by the weakening of soil layer strength. The field-monitoring results are consistent with the numerical simulation results, and the model calculation is reliable. This study plays an important role in ensuring construction safety and optimizing the construction risk control of a tunnel.